A new exTTF-crown ether platform to associate fullerenes: Cooperative n-π and π-π Effects - Grimm, Bruno; Santos, Jose; Illescas, Beatriz M.; Munoz, Antonio; Guldi, Dirk Michael; Martin, Nazario (Journal of the American Chemical Society, 2010)
A new and readily available exTTF-bis(crown ether), 1, efficiently recognizes C as well as C by means of cooperative π-π and n-π interactions. The geometrical (concave-convex) and electronic (donor-acceptor) complementarity accounts on one hand for remarkable binding strengths, with association constants reaching 10 M in benzonitrile, and on the other hand for lifetimes of the photogenerated radical ion pair state on the order of 45 ps. © 2010 American Chemical Society.